Report of the Task Force for Tackling the Problems of Scavengers and Suggesting Measures to Abolish Scavenging with Particular Emphasis on their Rehabilitation - Planning Commission (Planning Commission, 1990)
The report underscores the pressing need to eliminate scavenging as a practice by addressing its root causes, chiefly the existence of dry latrines. By implementing the outlined recommendations, it is expected that India can move towards a future where individuals who once engaged in scavenging can lead dignified lives, free from social stigma, and contribute positively to society. The Task Force is particularly optimistic that with sincere implementation and community involvement, India can achieve a scavenging-free society by the end of the decade.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Conversion of Latrines; Financial Outlay; Legal Measures; Employment Opportunities; Child Welfare and Education; Coordination among Agencies; Community Engagement; Monitoring and Evaluation; Social Stigma